On the Social Construction of Overdiagnosis; Comment on "Medicalisation and Overdiagnosis: What Society Does to Medicine" - Bjørn Hofmann (Kerman University of Medical Sciences, 2017)
In an interesting article Wieteke van Dijk and colleagues argue that societal developments and values influence the practice of medicine, and thus can result in both medicalisation and overdiagnosis. They provide a convincing argument that overdiagnosis emerges in a social context and that it has socially constructed implications. However, they fail to show that overdiagnosis per se is socially constructed and how this construction occurs. Moreover, the authors discuss overdiagnosis on a micro level without acknowledging that overdiagnosis cannot be observed in individuals "in the doctor's office." We cannot tell whether a diagnosed person is overdiagnosed or not. This is the core of the problem. Despite these shortcomings, Wieteke van Dijk and her colleagues are certainly on to something important, and they should be encouraged to elaborate their perspective. We certainly need to deepen our understanding of the social construction of overdiagnosis.